2017
DOI: 10.25046/aj020634
|View full text |Cite
|
Sign up to set email alerts
|

A Multilingual System for Cyberbullying Detection: Arabic Content Detection using Machine Learning

Abstract: With the abundance of Internet and electronic devices bullying has moved its place from schools and backyards into cyberspace; to be now known as Cyberbullying. Cyberbullying is affecting a lot of children around the world, especially Arab countries. Thus, concerns from cyberbullying are rising. A lot of research is ongoing with the purpose of diminishing cyberbullying. The current research efforts are focused around detection and mitigation of cyberbullying. Previously, researches dealt with the psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…In addition to the previous behaviors, cyberbullying is another serious issue that has been addressed by many researchers in English language. For the Arabic language, Haidar et al [64] made the first attempt to detect cyberbullying in Arabic language. Their work was the first step into this area, since it needs a lot of enhancements such as considering more features related to cyberbullying and choosing better feature representation.…”
Section: Arabic Anti-social Behaviour Detectionmentioning
confidence: 99%
“…In addition to the previous behaviors, cyberbullying is another serious issue that has been addressed by many researchers in English language. For the Arabic language, Haidar et al [64] made the first attempt to detect cyberbullying in Arabic language. Their work was the first step into this area, since it needs a lot of enhancements such as considering more features related to cyberbullying and choosing better feature representation.…”
Section: Arabic Anti-social Behaviour Detectionmentioning
confidence: 99%
“…Authors in [16], authors represented the first study in utilizing deep learning in Arabic cyberbullying detection .They utilized the same dataset in [17], with little changes. Changes include removing all hyperlinks, un-Arabic characters and emoticons.…”
Section: Detection In Arabic Languagementioning
confidence: 99%
“…Haidar et al in [17], suggested a system for detecting cyberbullying in English and Arabic text. The only features included in the first stage were text (content of tweet) and language (English, Arabic).…”
Section: Detection In Arabic Languagementioning
confidence: 99%
“…Moving on to Di Capua et al [9], they proposed a new way for cyberbullying detection by adopting an unsupervised approach, they used the classifiers inconsistently over their dataset, applying SVM on FormSpring and achieving 67% on recall, applying GHSOM on YouTube and achieving 60% precision, 69% accuracy and 94% recall, applying Naïve Bayes on Twitter and achieving 67% accuracy. Additionally, Haidar et al [10] proposed a model to detect cyberbullying but using Arabic language they used Naïve Bayes and achieved 90.85% precision and SVM achieved 94.1% as precision but they have high rate of false positive also the are work on Arabic language.…”
Section: Related Workmentioning
confidence: 99%